2022
DOI: 10.1002/anie.202206446
|View full text |Cite
|
Sign up to set email alerts
|

Facile Benzylic Alkylation of Arenes with Alcohols by Catalysis with Spirocyclic NHC IrIII Pincer Complex

Abstract: A facile benzylic alkylation of indenes and other arenes was developed from readily available primary and secondary alcohols using our newly investigated CCC pincer IrIII catalyst (SNIr−H). Excellent regioselectivity and yield (89 %) of the C3‐alkylated indenes were obtained. Additionally, the challenging sp2C‐alkylation was readily accomplished. This method could be utilized for the synthesis of the analogs of a histamine H1 receptor antagonist and the functional material template molecule, indeno[2,1‐a]inden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…An iridium-NHC pincer catalyst was employed by Tu in 2022 in the benzylic alkylation of activated arenes such as fluorene, xanthene, and methyl heteroarenes with primary and secondary alcohols (Scheme 54c). 342 The authors demonstrated the synthetic utility of this method in the synthesis of a histamine H1 receptor agonist. Finally, Zhao and colleagues demonstrated the redox-enabled direct enantioconvergent heteroarylation of simple alcohols in the presence of an achiral iridium catalyst and chiral phosphoric acid (Scheme 54d).…”
Section: Recent Reviewsmentioning
confidence: 99%
See 3 more Smart Citations
“…An iridium-NHC pincer catalyst was employed by Tu in 2022 in the benzylic alkylation of activated arenes such as fluorene, xanthene, and methyl heteroarenes with primary and secondary alcohols (Scheme 54c). 342 The authors demonstrated the synthetic utility of this method in the synthesis of a histamine H1 receptor agonist. Finally, Zhao and colleagues demonstrated the redox-enabled direct enantioconvergent heteroarylation of simple alcohols in the presence of an achiral iridium catalyst and chiral phosphoric acid (Scheme 54d).…”
Section: Recent Reviewsmentioning
confidence: 99%
“…Obora and colleagues extended this transformation to include the alkylation of methyl quinolines in subsequent years . Iridium catalysis has steadily remained the most utilized metal catalysis for the functionalization of alcohols through in situ carbonyl generation, proving useful in the functionalization of ketones, nitriles, , and C–H bonds. , …”
Section: Deoxygenative Functionalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we developed a novel spirocyclic N -heterocyclic carbene (SNHC)-based Ir­(III) CCC pincer complexes (SNIr-Cl), which showed excellent activities in C–H silylation, olefin isomerization, and borrowing hydrogen reactions. In these reactions, one of the Ph–Ir bonds cleaved and formed an Ir I species, which showed high reactivities in C–H bond activation and hydrogen borrowing hydrogen reactions.…”
Section: Introductionmentioning
confidence: 99%